Comparative Antimicrobial Activities of some Monosaccharide and Disaccharide Acetates - Matin, M. M.; Bhuiyan, M. M. H.; Afrin, A.; Debnath, D. C. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> A number of furanose (2,4) and pyranose (5,7,9,11,13) acetates were prepared by direct acetylation method. For comparative antimicrobial studies sucrose octaacetate (14) was also prepared. All the compounds (1-14) were screened for in vitro antibacterial activity against ten human pathogenic bacteria viz. Bacillus subtilis, Bacillus cereus, Bacillus megaterium, Staphylococcus aureus, Escherichia coli, INABA ET (Vibrio), Pseudomonas species, Salmonella paratyphi, Salmonella typhi and Shigella dysenteriae. These compounds were also screened for in vitro antifungal activity against four pathogenic fungi viz. Aspergillus niger, Alternaria alternata, Curvularia lunata and Fusarium equiseti. The study revealed that the pyranose acetate derivatives (5,7,9,11,13) are more prone towards antimicrobial functionality than those of the furanose acetates (2,4) and sucrose octaacetate (14). <p class="MsoNormal" style="margin-top: 0cm; margin-right: 14.2pt; margin-bottom: .0001pt; margin-left: 14.2pt; text-align: justify; line-height: 9.0pt; mso-line-height-rule: exactly; mso-pagination: none; page-break-after: avoid;"> <p class="MsoNormal" style="margin-top: 0cm; margin-right: 14.2pt; margin-bottom: .0001pt; margin-left: 14.2pt; text-align: justify; line-height: 9.0pt; mso-line-height-rule: exactly; mso-pagination: none; page-break-after: avoid;">Keywords: Glucofuranose; Glucopyranose; Acetylation; Antimicrobial activity; Structure activity relationship (SAR). © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.15695 J. Sci. Res. 5 (3), 515-525 (2013) <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->